Robotics: control and programming - SRINIVAS (J); DUKKIPATI (R V) (New Delhi Narosa Publishing House, 2012)
Robotics: Control and Programming covers primary concepts of principal robotic subsystems. Physical structure of manipulator mechanisms have been presented lucidly in the introductory chapter. Main types of sensors and actuators are illustrated in simple terms. Manipulator Kinematics, differential motion, dynamics and control are presented mathematically with a number of numerical examples. Different methods of robot programming are briefly discussed. Essential industrial applications of robots have been classified and grouped in the last chapter. Programmatically prepared manuscript allows the reader understand concepts of robotics and the simulation programs given in each chapter help in verification of many exercise problems of the book. Table Of Contents: Preface / Nomenclature